THE USE OF ENGLISH ANAGRAMS TO IMPROVE THE STUDENTS’ VOCABULARY TO THE FOURTH GRADE STUDENTS OF SDN 196 PALEMBANG - Nita Ria; Heru Setiawan (Universitas Tridinanti Palembang, 2020)
Vocabulary is one of the basic elements in mastering English. Vocabulary that plays a very important role in learning language because without vocabulary mastery, the students automatically can not obtain the four skills of English such as listening, reading, speaking and writing. This study was aimed to find out whether or not there was any significant difference in vocabulary mastery between the fourth grade students of SDN 196 Palembang who were taught by using English anagrams and those who were not. Fifty-six fourth graders were the sample of the study. In doing the study, an experimental method by using quasi-experimental design. The IV.A class became the experimental group and the IV.B class became the control group. A written test was the instrument to collect the data. The result showed that English anagarms had a significant effect on the students’ vocabulary mastery. Based on the independent sample t-test analysis, it was found that the significant level was 0.000 < 0.05, so that (Ha) was accepted and (Ho) was rejected. In other words, there was a significant difference on students’ vocabulary mastery between the fourth grade students of SDN 196 Palembang who were taught by using English anagram and those who were not.Keywords: English anagrams, vocabulary